Addressing dissention, limiting bureaucracy, and enhancing learning through assessment processes - Frederick Burrack; Ryan Chung; Shari Barrett (Academic Chairpersons Conference Proceedings, 2019)
This panel is an open conversation around strategies that brings together curriculum and instruction, data on student learning, and assessment practices that can lead to program improvements to enhance curriculum, teaching, and learning, as well as expose misconceptions of assessment practice and how assessment leaders can contribute to, or hinder student success.
Keywords: ment; Learning; Instruction; Curriculum; Collegiality